Seleção da tolerância à toxidez de alumínio em milho (Zea mays L.) - Alves Pinto Prioli, Sonia Maria; Silva, José Carlos; Domingos Galvão, José; Monnerat, Pedro Henrique; Prioli, Alberto José (Revista Ceres, 2025)
In this research, the corn variety, ‘Composto Dente’, was used as the base population (Cg). This variety was submitted to three cycles of selection for aluminum toxicity tolerance. The selection was done in nutrient solution with excess aluminum (6.75 ppm) as proposed by Rhue and Grogan, modified, and with the PpH adjusted daily to 4.6.